2010
DOI: 10.1007/s00284-010-9764-5
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of Escherichia coli Whole-Cell Biosensors for Toluene and Related Compounds

Abstract: The XylR regulatory protein is a transcriptional activator from the TOL plasmid of Pseudomonas putida mt-2 that is involved in the toluene and benzene degradation pathway. Here we describe the construction and laboratory characterization of recombinant biosensors (pGLPX plasmids) based on XylR and its cognate promoter (Pu). In the pGLPX plasmid, the reporter luc gene is under the control of the Pu promoter. We evaluated the ability of two distinct nucleotide sequences to function as SD elements and improve sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The Xyl R regulatory protein from Pseudomonas putida mt-2 TOL plasmid is involved in toluene and benzene degradation. Thus, the presence of toluene and its derivatives can be detected in soil [93]. Biosensorbased arrays are emerging as a new technology in the field of application of biosensors for detecting and monitoring pollutants.…”
Section: Desired Community and Its Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The Xyl R regulatory protein from Pseudomonas putida mt-2 TOL plasmid is involved in toluene and benzene degradation. Thus, the presence of toluene and its derivatives can be detected in soil [93]. Biosensorbased arrays are emerging as a new technology in the field of application of biosensors for detecting and monitoring pollutants.…”
Section: Desired Community and Its Performancementioning
confidence: 99%
“…Extraction of specific methyl ester profiles of microorganisms [22], [23] Quantitative PCR (qPCR) and RT-Q-PCR DNA/RNA Based on PCR, simultaneously amplifies and quantifies DNA/ RNA [27] Microbial degradative analysis Quantitative PCR (qPCR) and RT-Q-PCR DNA/RNA Based on PCR, simultaneously amplifies and quantifies DNA/ RNA [73], [74] DNA microarray DNA Arrays of DNA that hybridizes with specific target DNA strand [94] Monitoring of community structure Biosensors Nutrients like nitrogen, phosphorus, pollutants, toxic compounds Use of specific bioactive compound which emits signals [50], [93], [94], [95], [96] structures can be studied and compared by using DGGE profiles of PCR amplified products (16S and 18S rRNA genes) [17]. In addition, highly sensitive technique like terminal restriction fragment length polymorphism (T-RFLP) is also used for environmental samples [18].…”
Section: Methyl Esters From Lipidsmentioning
confidence: 99%
“…In this sensor, toluene activates the regulatory protein XylR that positively controls the Pu promoter, resulting in bioluminescence from the Pu::luc fusion. The ability of two distinct nucleotide sequences to function as SD elements and improve sensitivity of bioreporting was evaluated [20]; it was found that one (taaggagg) was far more effective than the other (aggaaa) in inducing reporter gene expression. A terminator placed in-frame and upstream of the Pu fragment minimized background expression of the luc gene, but also moderately reduced the intensity of the response.…”
Section: Genetic Manipulations Of the Sensing Elementmentioning
confidence: 99%
“…To enhance the sensitivity of bioreporting, the ability of two distinct nucleotide sequences functioning as SD elements and effect of introducing T 2 rrnβ terminator on the specifi city of the construct were evaluated. These manipulations showed that SD sequence (taaggagg) was important for biosensor sensitivity, but the presence of the T 2 rrnβ terminator reduced biosensor sensitivity after exposition to inducers -varied concentrations of nitrotoluenes [5].…”
Section: Reporter-genes Based Bacteria For Environmental Applicationsmentioning
confidence: 99%
“…Behzadian et al, 2011 [5] described the construction of recombinant biosensors where in the pGLPX plasmid, the reporter luc gene is under the control of the Pu promoter. To enhance the sensitivity of bioreporting, the ability of two distinct nucleotide sequences functioning as SD elements and effect of introducing T 2 rrnβ terminator on the specifi city of the construct were evaluated.…”
Section: Reporter-genes Based Bacteria For Environmental Applicationsmentioning
confidence: 99%